Age‐dependent loss of parvalbumin‐expressing hippocampal interneurons in mice deficient in CHL1, a mental retardation and schizophrenia susceptibility gene. (8th September 2015) - Schmalbach, Barbara; Lepsveridze, Eka; Djogo, Nevena; Papashvili, Giorgi; Kuang, Fang; Leshchyns'ka, Iryna; Sytnyk, Vladimir; Nikonenko, Alexander G.; Dityatev, Alexander; Jakovcevski, Igor; Schachner, Melitta
Abstract: In humans, deletions/mutations in the CHL1/CALL gene are associated with mental retardation and schizophrenia. Juvenile CHL1‐deficient ( CHL1 −/− ) mice have been shown to display abnormally high numbers of parvalbumin‐expressing (PV + ) hippocampal interneurons and, as adults, display behavioral traits observed in neuropsychiatric disorders. Here, we addressed the question whether inhibitory interneurons and synaptic plasticity in the CHL1 −/− mouse are affected during brain maturation and in adulthood. We found that hippocampal, but not neocortical, PV + interneurons were reduced with age in CHL1 −/− mice, from a surplus of +27% at 1 month to a deficit of ‐20% in adulthood compared with wild‐type littermates. This loss occurred during brain maturation, correlating with microgliosis and enhanced interleukin‐6 expression. In parallel with the loss of PV + interneurons, the inhibitory input to adult CA1 pyramidal cells was reduced and a deficit in short‐ and long‐term potentiation developed at CA3–CA1 excitatory synapses between 2 and 9 months of age in CHL1 −/− mice. This deficit could be abrogated by a GABAA receptor agonist. We propose that region‐specific aberrant GABAergic synaptic connectivity resulting from the mutation and a subsequently enhanced synaptic elimination during brain maturation lead to microgliosis, increase in pro‐inflammatory cytokine levels, loss of interneurons, and impaired synaptic plasticity. Close homolog of L1‐deficient ( CHL1 −/− ) mice have abnormally high numbers of parvalbumin (PV)‐expressing hippocampal interneurons in juvenile animals, but in adult animals a loss of these cells is observed. This loss correlates with an increased density of microglia (M), enhanced interleukin‐6 (IL6) production and a deficit in short‐ and long‐term potentiation at CA3–CA1 excitatory synapses. Furthermore, adult CHL1 −/− mice display behavioral traits similar to those observed in neuropsychiatric disorders of humans. Abstract : Close homolog of L1‐deficient ( CHL1 −/− ) mice have abnormally high numbers of parvalbumin (PV)‐expressing hippocampal interneurons in juvenile animals, but in adult animals a loss of these cells is observed. This loss correlates with an increased density of microglia (M), enhanced interleukin‐6 (IL6) production and a deficit in short‐ and long‐term potentiation at CA3–CA1 excitatory synapses. Furthermore, adult CHL1 −/− mice display behavioral traits similar to those observed in neuropsychiatric disorders of humans.